(untitled) (Research, Society and Development, 2020)
Management Information Systems (GIS) are a strategic tool in organizational management, by providing information that contributes to the systematization of internal processes and underpins the decision-making of companies regardless of size or industry. In this sense, the present study aims to describe the activities inherent to the analysis and gradual modeling of an application on the Android platform, of operational assistance for hotels. Methodologically, the study is classified as being of a qualitative nature, through the realization of a case study in the municipality of Iporá in Goiás, to collect the information that helped in the business modeling process, use case diagram and diagram of class in order to transform the information collected into technical information for the development of the application. It was found, therefore, that the development and use of tools such as the use of applications, contributes to the execution of daily activities, focusing on the identified priorities.